Cultivating Metacognitive Awareness through Self-Assessment: An Instrument for Evaluating Four Language Skills in Arabic Learning - Dina Mutiatunnisa; Moh. Ainin; Nurul Murtadho (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2025)
Affective domain assessment in Arabic language learning is still rarely done systematically due to time constraints and teacher confusion over assessment indicators. As a result, students are less involved in reflective processes that support learning awareness and self-regulation. This study aims to develop a self-assessment instrument on the four Arabic language skills (listening, speaking, reading, and writing), which also train students' metacognitive abilities. The research method employed is the Borg and Gall development steps by adapting them into four steps: Research and information collecting, planning, product development, and validity test. This research produces a self-assessment instrument that combines the Arabic textbook of the Ministry of Religious Affairs (2020) and the competency standards of KMA 183 (2019) for the four Arabic language skills. The self-assessment instrument contains: 1) title; 2) instructions for filling; 3) student identity; 4) theme and basic competencies that must be achieved; and 5) self-assessment questionnaire. The validation results from the three validators indicated that the self-assessment instrument was valid and appropriate for use in assessing students’ proficiency in Arabic language learning.